Effect of Candida albicans and Candida dubliniensis planktonic/biofilm quorum sensing molecules on yeast morphogenesis - Henriques, Mariana (2006)
One of the aims of this work was to study the effect of farnesol, a quorum sensing molecule for Candida albicans, on morphologic inhibition of Candida dubliniensis. The second goal of this work was to confirm if Candida dubliniensis also excreted quorum sensing molecules, on both planktonic and biofilm forms. The results clearly demonstrate that Candida dubliniensis undergoes morphological alterations triggered by farnesol. It was also found that supernatants of Candida dubliniensis and Candida albicans grown in both planktonic or biofilm forms contain molecules that are capable of suppressing pseudohyphae formation on Candida dubliniensis cells grown in RPMI 1640. It can be concluded that both Candida dubliniensis and Candida albicans produces quorum sensing molecules either in planktonic or biofilm forms, which regulates Candida dubliniensis morphology.